Aerobic Interval Training Attenuates Mitochondrial Dysfunction in Rats Post-Myocardial Infarction: Roles of Mitochondrial Network Dynamics - Jiang, Hong-Ke (Molecular Diversity Preservation International (MDPI), 2014)
Aerobic interval training (AIT) can favorably affect cardiovascular diseases. However, the effects of AIT on post-myocardial infarction (MI)—associated mitochondrial dysfunctions remain unclear. In this study, we investigated the protective effects of AIT on myocardial mitochondria in post-MI rats by focusing on mitochondrial dynamics (fusion and fission). Mitochondrial respiratory functions (as measured by the respiratory control ratio (RCR) and the ratio of ADP to oxygen consumption (P/O)); complex activities; dynamic proteins (mitofusin (mfn) 1/2, type 1 optic atrophy (OPA1) and dynamin-related protein1 (DRP1)); nuclear peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α); and the oxidative signaling of extracellular signal-regulated kinase (ERK) 1/2, c-Jun NH(2)-terminal protein kinase (JNK) and P53 were observed. Post-MI rats exhibited mitochondrial dysfunction and adverse mitochondrial network dynamics (reduced fusion and increased fission), which was associated with activated ERK1/2-JNK-P53 signaling and decreased nuclear PGC-1α. After AIT, MI-associated mitochondrial dysfunction was improved (elevated RCR and P/O and enhanced complex I, III and IV activities); in addition, increased fusion (mfn2 and OPA1), decreased fission (DRP1), elevated nuclear PGC-1α and inactivation of the ERK1/2-JNK-P53 signaling were observed. These data demonstrate that AIT may restore the post-MI mitochondrial function by inhibiting dynamics pathological remodeling, which may be associated with inactivation of ERK1/2-JNK-P53 signaling and increase in nuclear PGC-1α expression.